The effects of strain and composition on the conduction-band offset of direct band gap type-I GeSn/GeSnSi quantum dots for CMOS compatible mid-IR light source - Chen, Qimiao (2020)
A direct band gap type-I Ge0.75Sn0.25/Ge0.682Sn0.158Si0.16 QD heterostructure is proposed for mid-IR light sources. The effects of strain and composition are theoretically investigated to optimize the band offset of the direct band gap GeSn QDs. It is found that the introduction of tensile strain and Si incorporation in the barrier layers are effective to increase the band offset in the conduction band. Besides, the band offset is expected to increase with the increase of Sn composition in QDs and the size of QDs.